Molecular Modeling Study of Uncharged Oximes Compared to HI-6 and 2-PAM Inside Human AChE Sarin and VX Conjugates - Souza, Felipe Rodrigues de; Rodrigues Garcia, Danielle; Cuya, Teobaldo; Pimentel, André Silva; Gonçalves, Arlan da Silva; Alencastro, Ricardo Bicca de; França, Tanos Celmar Costa (ACS omega, 2020)
The deleterious effects of nerve agents over the enzymes acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) turned these compounds into the most dangerous chemical weapons known. Among the antidotes in use today against these agents, oximes in combination with other drugs are the only treatment with any action. HI-6 and 2-PAM are cationic oximes proved to be effective for the reactivation of AChE inhibited by the nerve agents VX and sarin (GB). However, when it comes to reactivation of AChE inside the central or peripheral nervous systems, charged molecules present low diffusion due to low penetration through the blood-brain barrier. Uncharged oximes appear as an interesting alternative to solve this problem, but the development and enhancement of more efficient uncharged oximes capable of reactivating human AChE is still necessary. Given the limitations for in vivo and in vitro experimental studies with nerve agents, modeling is an important tool that can contribute to a better understanding of factors that may affect the efficiency of uncharged oximes. In order to investigate the interaction and behavior of cationic and uncharged oximes, we performed here molecular docking, molecular dynamics simulations, and binding energies calculations of the known cationic oximes HI-6 and 2-PAM plus four uncharged oximes found in the literature, complexed with human AChE (HssACHE) conjugated with the nerve agents VX and GB. The uncharged oximes showed different behaviors, especially RS194B, which presented stability inside AChE-VX, but presented free binding energy lower than cationic oximes, suggesting that structural alterations could favor its interactions with these complexes. In contrast, HI-6 and 2-PAM showed higher affinities with more negative binding energy values and larger contribution of the amino acid Asp74, demonstrating the importance of the quaternary nitrogen to the affinity and interaction of oximes with AChE-GB and AChE-VX conjugates.